Quantifying the probability of existential catastrophe: A reply to Beard et al. (October 2020) - Baum, Seth D.
Highlights: The probability of existential catastrophe is inherently linked to the severity. Achieving a high quality analysis requires investment. Probability analysis is sometimes but not always necessary for decision-making. Analysis should support risk management. Abstract: A recent article by Beard, Rowe, and Fox (BRF) evaluates ten methodologies for quantifying the probability of existential catastrophe. This article builds on BRF's valuable contribution. First, this article describes the conceptual and mathematical relationship between the probability of existential catastrophe and the severity of events that could result in existential catastrophe. It discusses complications in this relationship arising from catastrophes occurring at different speeds and from multiple concurrent catastrophes. Second, this article revisits the ten BRF methodologies, finding an inverse relationship between a methodology's ease of use and the quality of results it produces—in other words, achieving a higher quality of analysis will in general require a larger investment in analysis. Third, the manuscript discusses the role of probability quantification in the management of existential risks, describing why the probability is only sometimes needed for decision-making and arguing that analyses should support real-world risk management decisions and not just be academic exercises. If the findings of this article are taken into account, together with BRF's evaluations of specific methodologies, then risk analyses of existential catastrophe may tend to be more successful at understanding and reducing the risks.